Public archaeology cannot just ‘fly at dusk’: the reality and complexities of generating public impact - Bonacchi, Chiara (Antiquity, 2018)
In his debate piece ‘The Brexit hypothesis and prehistory’, Kenneth Brophy (2018) foregrounds some of the possible consequences of archaeology's media and public exposure. While recognising that (mis)appropriations of research for political purposes are nothing new, he stresses that these instrumental uses might have been amplified by a more interconnected web. Brophy emphasises that people are frequently presented with, and consume, archaeological findings in ways that often inappropriately relate the latter to contemporary social issues, such as Brexit. His proposed solution to the problem is twofold. On the one hand, he recommends that archaeologists should ‘push back’ against erroneous and hyperbolic accounts of their work featuring in the media and in public online discussions. On the other hand, he encourages archaeologists to ‘pre-empt’ such interpretations, drawing on insights derived from social research aimed at understanding how modern individuals and groups interact with the past. While I agree with the author that these measures are welcome and valuable, I believe that they cannot provide, on their own, a ‘solution’. They are laudable from a deontological point of view—in principle, they can be viewed as responsible and ethical practice—but do not consider the full reality of the world of media and communications, nor the ways in which people actually leverage the past when making sense of situations that concern them. Here, I briefly expand on both of these points and argue that the dynamics of generating impact are complex and lengthy. Influencing public opinion requires more substantial and profound public engagement on the part of ‘public intellectuals’, as Brophy calls them, than is suggested in his paper.